The novel immunosuppressive protein kinase C inhibitor sotrastaurin has no pro-viral effects on the replication cycle of hepatitis B or C virus - Hahn, Thomas von; Schulze, Andreas; Wust, Ivan Chicano; Heidrich, Benjamin; Becker, Thomas; Steinmann, Eike; Helfritz, Fabian A.; Rohrmann, Katrin; Urban, Stephan; Manns, Michael P.; Pietschmann, Thomas; Ciesek, Sandra (PLOS ONE, 2011)
The pan-protein kinase C (PKC) inhibitor sotrastaurin (AEB071) is a novel immunosuppressant currently in phase II trials for immunosuppression after solid organ transplantation. Besides T-cell activation, PKC affects numerous cellular processes that are potentially important for the replication of hepatitis B virus (HBV) and hepatitis C virus (HCV), major blood-borne pathogens prevalent in solid organ transplant recipients. This study uses state of the art virological assays to assess the direct, non-immune mediated effects of sotrastaurin on HBV and HCV. Most importantly, sotrastaurin had no pro-viral effect on either HBV or HCV. In the presence of high concentrations of sotrastaurin, well above those used clinically and close to levels where cytotoxic effects become detectable, there was a reduction of HCV and HBV replication. This reduction is very likely due to cytotoxic and/or anti-proliferative effects rather than direct anti-viral activity of the drug. Replication cycle stages other than genome replication such as viral cell entry and spread of HCV infection directly between adjacent cells was clearly unaffected by sotrastaurin. These data support the evaluation of sotrastaurin in HBV and/or HCV infected transplant recipients.
Gesehen am 02.11.2022